Rediscovery and a new record of Hemidactylus laevis (Reptilia: Gekkonidae) from Somaliland, with notes on and resurrection of Hemidactylus fragilis - Mazuch, Tomáš; Šmíd, Jiří; Bauer, Aaron M. (Zootaxa, 2016)
Hemidactylus laevis, a gekkonid lizard originally described from the Gaan Libah Mountains in Somaliland, is recorded herein from Erigavo, Sanaag Region, in the same state, which represents the second-ever known specimen and locality for this species in more than 100 years since its description. The species is endemic to Somaliland. Data on morphology and natural history, as well as the first life photographs are provided. Based on morphological data we conclude the species to be closely related to H. laticaudatus. Additionally, H. fragilis from southern Somalia and extreme south-east Ethiopia is resurrected from the synonymy of H. frenatus based on morphological data.